Rhetorical move and genre knowledge development of English and Indonesian abstracts: A comparative analysis - Syifa Nanda Pratiwi; Eri Kurniawan (Studies in English Language and Education, 2021)
A plethora of research has shown that genre analysis through move analysis is a practical approach to identify the complexity of writing research articles (RAs). However, little is known about the genre knowledge development that is manifested in abstract discourse patterns. This study aims to determine whether or not there is an influence from the level of education with the development of genre knowledge, especially in the field of writing research abstracts. Using Hyland’s (2000) five-move analysis model, this study analyzed the comparison and identity of abstracts of theses and dissertations in English and Indonesian. From the analysis, it can be seen that there are some differences and similarities in the manifestation of abstract discourse patterns in English and Indonesian final paper abstracts. In terms of genre knowledge, its development could be reflected through the level of study, in this case, from master’s to doctoral degrees. As evident in the dissertation abstracts in both languages, Move 1 (Introduction) evinces richer varieties in step realizations than in master’s theses. The analysis also indicates no crucial differences in genre knowledge development across languages and fields of study. Further comparative research on this particular topic with more subject of data is suggested.